# Precalculus

1.Write the expression as a sum or difference.
cos(5x)cos(-4x)
2.Write the expression as a product.
cos(4x)-cos(12x)

1. 👍 0
2. 👎 0
3. 👁 151
1. 1. use
cos(a)+cos(b)=2[cos((a+b)/2)cos((a-b)/2)]
and set a=x/2, b=9x/2

2. use
cos(a)-cos(b)=-2[sin((a+b)/2)sin((a-b)/2)]
and set a=-4x, b=8x

Hint: before doing the work, check the formulas using some trivial cases such as a=π/2, and b=π/4.

1. 👍 0
2. 👎 0
posted by MathMate

## Similar Questions

1. ### Precalculus

1.Write the expression as a sum or difference. cos(5x)cos(-4x) 2.Write the expression as a product. cos(4x)-cos(12x)

asked by Lynette on December 5, 2010
2. ### Math

1. use the suitable product-to-sum formula to rewrite the following expression: sin(13x/2)sin(5x/2) 2. Find value of cos(255degrees)cos(105degrees) is it 1/4? 3. cos(pi/12) - cos(5pi/12) root3/4? 4. Use the appropriate

asked by mysterychicken on June 3, 2013
3. ### Math

Can someone please check my answers! 2. Find value of cos(255degrees)cos(105degrees) root3 - 2 / 4 3. cos(pi/12) - cos(5pi/12) Is it root3/4? 4. Use the appropriate sum-to-product formula to rewrite the expression sin6x - sin9x I

asked by mysterychicken on June 3, 2013
4. ### pre-cal

Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos 6x can be expressed as a series of terms that involve sin x or cos x only, but the end result is not a simplification. sin 2x = 2 sinx cosx cos 6x = 32 cos^6 x

asked by ethan on May 17, 2007
5. ### TRIG!

Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x +

asked by hayden on February 23, 2009
6. ### Math

Write the expression in terms of costheta and then simplify. cos^4theta - sin^4theta + sin^2theta Ans: cos^4 θ - 1 - cos^4 θ + 1 - cos^2 θ = -cos^2 θ

asked by Anonymous on June 2, 2015
7. ### Trigonometry

Use a sum of difference identity to write the expression as a single function theta: cos(theta - pi). Okay so I know we will use cosAcosA+sinBsinB I got: cos(theta)cos(theta)sin(pi)sin(pi) I don't know how to solve from here and

asked by Abby on February 29, 2016
8. ### Pre-Cal (Trig) Help?

The following relationship is known to be true for two angles A and B: cos(A)cos(B)-sin(A)sin(B)=0.957269 Express A in terms of the angle B. Work in degrees and report numeric values accurate to 2 decimal places. So I'm pretty

asked by Giovanni on May 6, 2016
9. ### Trigonometry

Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)

asked by anon on March 3, 2011
10. ### algebra

Can someone please help me do this problem? That would be great! Simplify the expression: sin theta + cos theta * cot theta I'll use A for theta. Cot A = sin A / cos A Therefore: sin A + (cos A * sin A / cos A) = sin A + sin A = 2

asked by Valerie on February 18, 2007

More Similar Questions